Treatment outcomes of posterior pilon fractures using a simple single lateral approach via stretching fibular fracture line - Liang, Wei; Zhou, Mingping; Jiang, Zhongting; Mao, Xuanyu; Zhou, Xiang (Frontiers in Surgery, 2023)
Purpose: The aim of this study was to explore the treatment outcomes of a novel single lateral approach via fibular fracture line for patients with posterior pilon fractures. Patients and Methods: From Jan 2020 to Dec 2021, a total of 41 patients with posterior pilon fractures who received surgical treatment in our hospital were retrospectively reviewed. Twenty patients (Group A) were treated with open reduction and internal fixation (ORIF) via posterolateral approach. Twenty-one patients (Group B) were treated with ORIF using a simple single lateral approach via stretching fibular fracture line. Clinical assessments, including operation time, intraoperative blood loss, the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score, visual analogue scale (VAS), and the active range of motion (ROM) of the ankle at the final follow‑up visit after surgery, were performed in all patients. Radiographic outcome was evaluated by using the criteria proposed by Burwell and Charnley. Results: The mean follow-up time was 21 months (range 12-35). The average operation time and intraoperative blood loss in the Group B were significantly less than those in the Group A. Moreover, the AOFAS score and ankle ROM in the Group B were significantly higher than those in the Group A at the final follow‑up visit. Eighteen cases (90%) in Group A and 19 cases (90.5%) in Group B achieved anatomical reduction of the fracture. Conclusion: The single lateral approach via stretching fibular fracture line is a simple and effective technique for reduction and fixation of posterior pilon fractures.